Drug Related Problem (DRP) of Dengue Hemorragic Fever (DHF) medication in pediatric patient` - Yasin, Nanang Munif; Sunowo, Joko; Supriyanti, Eri (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Every year, Dengue Hemorrhagic Fever (DHF) is the big problem Indonesianâs government with high incidency and high mortality. It would increased length of stay and high cost. The objectives of this study are to identify drug-related problems in DHF patient include need for additional drug therapy, unnecessary drug therapy, wrong drug, drug interaction, dosage to high, and dosage too low.A prospective study of pediatrics admitted to Pediatric Ward, X Private Hospital Yogyakarta for DHF infections was carried out since February-April 2006. Appropriate descriptive analysis was used.The results showed that unnecessary drug therapy the most drugrelated problems in 22 patient from 65 pediatic patient.The other DRP were dosage too low in 14 patient, dosage too high in 10 patient, wrong drug in 4 patient, and need for additional drug therapy in 2 patient, rescpectively. Antibiotics were the most cause of drug-related problems in DHF patient.Key words : Dengue Hemorrhagic Fever (DHF), Drug-Related Problem (DRP), Antibiotic , Hospital.